2018
DOI: 10.1007/s40820-018-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photoelectrochemical Water Splitting by g-C3N4/TiO2 Nanotube Array Heterostructures

Abstract: Well-ordered TiO2 nanotube arrays (TNTAs) decorated with graphitic carbon nitride (g-C3N4) were fabricated by anodic oxidization and calcination process. First, TNTAs were prepared via the anodic oxidation of Ti foil in glycerol solution containing fluorinion and 20% deionized water. Subsequently, g-C3N4 film was hydrothermally grown on TNTAs via the hydrogen-bonded cyanuric acid melamine supramolecular complex. The results showed that g-C3N4 was successfully decorated on the TNTAs and the g-C3N4/TNTAs served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(63 citation statements)
references
References 57 publications
2
56
1
Order By: Relevance
“…A similar concept of heterojunctions of TiO 2 and g-C 3 N 4 has been raised by Liu et al [58] through the anodizing of titanium foil to form TiO 2 nanotube arrays (TNTAs) then decorating with g-C 3 N 4 . For comparison, amorphous TiO 2 , Ti foil without anodic oxidation treatment was also investigated.…”
Section: Graphitic Carbon Nitridementioning
confidence: 86%
See 1 more Smart Citation
“…A similar concept of heterojunctions of TiO 2 and g-C 3 N 4 has been raised by Liu et al [58] through the anodizing of titanium foil to form TiO 2 nanotube arrays (TNTAs) then decorating with g-C 3 N 4 . For comparison, amorphous TiO 2 , Ti foil without anodic oxidation treatment was also investigated.…”
Section: Graphitic Carbon Nitridementioning
confidence: 86%
“…The pyridinic and quaternary nitrogen atoms act as active sites for chemical reactions, making g-C 3 N 4 a favorable catalyst in water splitting reactions [36]. Considerable work has been done to optimize its performance, such as doping, forming heterojunctions [58,59], metal nanoparticle decoration, and copolymerization. A g-C 3 N 4 powder can be easily synthesized via inexpensive raw materials, such as urea, melamine, dicyandiamide, under high temperatures, further adding to its advantages as a catalyst in water splitting reactions [23,24].…”
Section: Graphitic Carbon Nitridementioning
confidence: 99%
“…Figure 8c shows the open-circuit photovoltage curves, suggesting the n-type conductivity of all samples [48]. The negative increase in voltage under light irradiation suggested that the photogenerated electrons are injected from the semiconductor film into the Ti substrate [49]. The open-circuit potential has increased with the loading of Ag NPs, while a slight decrease of about 0.03 V has been observed with the addition of rGO in nanotubes and nanorings.…”
Section: Photoelectrochemical Properties and Hydrogen Production Ratesmentioning
confidence: 97%
“…The process of solution coating and subsequent calcination is widely used in the synthesis of core/shell structures [193,[201][202][203]. The coating mainly involves a mixed precursor solution and a simplex salt solution.…”
Section: Type-ii Junctionmentioning
confidence: 99%